Creating effective brand names with sound symbolic mappings - Trninić Zora (Strategic Management, 2023)
Background: The present study was designed to investigate the use of sound symbolic mappings in fictitious brand names. Sound symbolic mappings refer to the existence of a nonarbitrary relationship between individual sounds and associations of different attributes and concepts. Given that sounds have inherent meaning in them, brand names in line with the established symbolic effects could communicate tailored messages that are congruent with consumer expectations of a product. Purpose: As perceived congruency between a product and its label is highly desirable in marketing, the study sets out to test the noted effects in brand names. It was aimed to confirm the strength of sound symbolic effects through greater preference for names with a symbolic fit with the product. Study design/methodology/approach: Two product categories were chosen, and a set of fictitious brand names were created. The names differed only on the sounds purported to convey targeted symbolic associations of salient product characteristics. The participants were presented with a forced choice task consisting of paired name samples and a stated product category for each pair. Finding/conclusions: The results confirmed the presence of sound symbolic effects as participants favoured the names with embedded symbolism. This leads to a conclusion that sound symbolism may be used to affect consumer choices based on brand name preference. Limitations/future research: Even though the study included only two products and used forced choice tasks limited on name pairs, the findings clearly imply the potential of sound symbolic mappings in creating efficient brand names. Broadening the research to other products and the service sector would surely deliver intriguing results.